Influence of the aerodynamic flow on the dynamic characteristics of a lightning sweeping arc - Xiao, Cien; Liu, Yakun (Frontiers in Astronomy and Space Sciences, 2023)
Lightning arc attachments during swept strokes are key information in the lightning protection design of fast-moving aircraft, wind turbines, rockets, etc. However, numerical modeling has not achieved success to predict the movement of lightning sweeping arcs due to the limited understanding of the complex multi-physics convolution in the arc fluid at present. This work builds a dynamic magneto-hydrodynamic (MHD) arc model based on the setup in the laboratory simulation of the lightning continuing current and couples the electric–magnetic–thermal–force processes to get insights into the lightning arc dynamics. The MHD theory and Newton’s second law of motion are also incorporated to describe the movement of arc segments in the conditions of aerodynamic flows with different intensities. Results show that, at the center region of the arc, the electromagnetic force, thermal buoyancy, and aerodynamic force are competitive, and all are determiners in predicting the arc displacement. In contrast, at the root region of the arc, the electromagnetic force dominates the arc movement with a flow speed under 10 m/s, while aerodynamic force takes the dominant role when the flow speed exceeds 50 m/s. The arc sweeping distance expands from 0.02 to 1.01 m as the aerodynamic flow increases from 5 to 200 m/s. Meanwhile, when increasing the pitch angle of the arc-connected surface, the arc root becomes more attached to the surface and the sweeping distance is predicted to get reduced. The conclusions offer references to construct a numerical model and predict the complex arc movement during lightning sweeping strokes.